Levelling up in a ‘decentralised’ England: place-based or ‘one-size-fits-all’ strategies? - Shivani Sickotra (Regional Studies, Regional Science)
English policymaking has traditionally been centralised, assuming homogenous needs across regions and contributing to economic inequalities. The Levelling Up Agenda aims to address these disparities through a place-based approach using devolved Combined Authority (CA) organisations. Despite being the first national strategy with an extensive place-based focus, it faces criticism as a potentially centralised political tool. Concerns also exist about whether Combined Authorities can deliver regional economic development as they have centrally controlled aspects. If regional planning approaches are identical, decentralisation through Combined Authorities would essentially be futile. This paper uses a novel quantitative method with Strategic Economic Plans to determine if regional planning inhibits a place-based or ‘one-size-fits-all’ approach, contributing data-driven insights to the debate regarding the efficacy of Combined Authorities. Through exploratory text analysis, hierarchical and K-means clustering, findings indicate regions adopt place-sensitive planning with varying sector priorities. A northern-southern and an inland-coastal distinction emerge, with London as an outlier. This suggests Combined Authorities are fit for purpose at this quantitative clustering level and do consider their geographical context in planning despite a devolved yet centrally controlled oxymoronic landscape. Collaborations like an inland and a coastal CA network are recommended to potentially maximise place-based growth.